A Merged Model of Quality Improvement and Evaluation: Maximizing Return on Investment. Issue 6 (November 2013) - Woodhouse, Lynn D.; Toal, Russ; Nguyen, Trang; Keene, DeAnna; Gunn, Laura; Kellum, Andrea; Nelson, Gary; Charles, Simone; Tedders, Stuart; Williams, Natalie; Livingood, William C.
Quality improvement (QI) and evaluation are frequently considered to be alternative approaches for monitoring and assessing program implementation and impact. The emphasis on third-party evaluation, particularly associated with summative evaluation, and the grounding of evaluation in the social and behavioral science contrast with an emphasis on the integration of QI process within programs or organizations and its origins in management science and industrial engineering. Working with a major philanthropic organization in Georgia, we illustrate how a QI model is integrated with evaluation for five asthma prevention and control sites serving poor and underserved communities in rural and urban Georgia. A primary foundation of this merged model of QI and evaluation is a refocusing of the evaluation from an intimidating report card summative evaluation by external evaluators to an internally engaged program focus on developmental evaluation. The benefits of the merged model to both QI and evaluation are discussed. The use of evaluation based logic models can help anchor a QI program in evidence-based practice and provide linkage between process and outputs with the longer term distal outcomes. Merging the QI approach with evaluation has major advantages, particularly related to enhancing the funder's return on investment. We illustrate how a Plan-Do-Study-Act model of QI can (a) be integrated with evaluation based logic models, (b) help refocus emphasis from summative to developmental evaluation, (c) enhance program ownership and engagement in evaluation activities, and (d) increase the role of evaluators in providing technical assistance and support.